2023
DOI: 10.1002/cam4.5896
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically defined body size and body shape phenotypes and risk of postmenopausal breast cancer in the European Prospective Investigation into Cancer and Nutrition

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Several pathways have been proposed through which IR may have pro-oncogenic, mitogenic, and antiapoptotic effects [133,134]. In fertile women, insulin and IGF-1 inhibit the hepatic synthesis of sex hormone-binding globulin (SHBG), increasing the bioavailability of estrogen, which may account for the increased risk of breast cancer [135,136]. The proinflammatory state and the consequent increased production of free oxygen radicals (ROS) represent a favorable environment for the development and progression of neoplasms inducing mutagenesis and carcinogenesis [137].…”
Section: Insulin Resistance and Cancermentioning
confidence: 99%
“…Several pathways have been proposed through which IR may have pro-oncogenic, mitogenic, and antiapoptotic effects [133,134]. In fertile women, insulin and IGF-1 inhibit the hepatic synthesis of sex hormone-binding globulin (SHBG), increasing the bioavailability of estrogen, which may account for the increased risk of breast cancer [135,136]. The proinflammatory state and the consequent increased production of free oxygen radicals (ROS) represent a favorable environment for the development and progression of neoplasms inducing mutagenesis and carcinogenesis [137].…”
Section: Insulin Resistance and Cancermentioning
confidence: 99%
“…high fasting insulin, high HOMA-IR, hepatic steatosis), had elevated breast cancer risk irrespective of BMI ( 64 66 ). However, a very recent study indicated no difference in postmenopausal breast cancer risk in women classified as metabolically healthy overweight/obese or as metabolically unhealthy lean using C-peptide measures ( 67 ). Deteriorating metabolic function may indicate the presence of prediabetes, which is characterized by sustained hyperinsulinemia.…”
Section: The Impact Of Metabolic Health On Breast Cancer Risk and Pro...mentioning
confidence: 99%